P-3 Developing skills to plan for the future. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Stanley, Sarah; Dynes, Bill; Bonwick, Helen; Pryce, Ruth; Mills, Mark; Williams, Shirley; Jones, Caroline; Warr, Beth
Abstract : Background: Research suggests that Advance Care Planning (ACP) improves quality of life and leads to better outcomes for both patients and their families. However, evidence suggests that these sensitive conversations often do not occur (Cottingham, Beck-Coon, Bernat, Helft et al ., 2019). Healthcare professionals require support and training around advance care planning to enable them to feel confident engaging in such discussions (Barnes, Barlow, Harrington, Ornadel et al ., 2011). Aim: Our aim was to improve the opportunities for hospice patients to participate in advance care planning conversations. Methods: Two members of the nursing team were trained locally in the delivery of advance care planning teaching sessions, which aim to prepare staff when entering into these sensitive conversations. We then developed a focus group of multi-disciplinary team (MDT) members to discuss barriers to advance care planning, and how we could best improve the frequency of these conversations within the hospice. Documentation was reviewed within the group, and a process of monitoring the use and effectiveness of this documentation was agreed. Discussions around embedding advance care planning into the admissions process and weekly MDT meetings are underway. Posters were developed for patient areas to encourage patients and caregivers to ask about advance care planning. Results: So far results have been positive. Hospice staff have reported finding teaching sessions useful, and a new feeling of confidence towards approaching advance care planning conversations. We have seen evidence of more advance care planning conversations taking place throughout the hospice. Developing a focus group has allowed us to work at standardising practice throughout the hospice (both inpatient and outpatient units), and to feedback on progress. Conclusions: Our work has demonstrated that by educating and supporting our staff, use of advance care planning documentation within the hospice has started to increase. So far feedback from patients has been positive. Work is ongoing. We hope that by developing the skills and confidence of our staff we will provide hospice patients with greater opportunity to discuss their plans for the future.